The social fabric of a debt economy: Mexican immigrants in the 2008 mortgage crisis - Magdalena Villarreal (economic sociology_the european electronic newsletter, 2018)
In July 2007 massive losses began to afflict world stock markets. The disaster was sparked by the revelation of what many already knew but preferred to ignore, namely that vast swathes of mortgage- backed financial instruments that had hitherto been a runaway success were based on loans that would never be repaid. Such instruments, designed by Wall Street financial engineers to satisfy the appetite for risk of millions of investors, had produced juicy profits for many, but were now discovered to be largely backed by thin air. In California, one of the most critical US states involved in the mortgage crisis, a substantial proportion of the unpayable loans had been issued to African-Americans and immigrant Mexicans...
Keywords: 330